Persepsi Siswa Terhadap Implementasi Kurikulum 2013 di SMK Negeri 1 Sumatera Barat - Muhammad Naufal; Martias Martias (AEEJ : Journal of Automotive Engineering and Vocational Education, 2020)
This research aims to investigate the students' perception of class XI towards implementing the 2013 Curriculum at Light Vehicle Engineering Competence in SMK Negeri 1 Sumatera Barat. The type of this research is quantitative descriptive. Based on the results that have been analyzed, it can be concluded that the perception of Class XI students towards the implementation of the 2013 Curriculum at Light Vehicle Engineering Competency in SMK Negeri 1 Sumatera Barat is in the well-implemented category (65.38%). It is categorized into six indicators; Learning Model in the well-implemented category (65.38); Core Competencies in the well-implemented category (50.00%); Scientific approach in the well-implemented category (59.62%); Class organizing in the very well implemented category (67.31%); The use of infrastructure in the well-implemented category(67.31%); Evaluating in the well-implemented category (32.69%). Tujuan penelitian ini untuk mengetahui bagaimana persepsi siswa kelas XI terhadap Implementasi Kurikulum 2013 Kompetensi Keahlian Teknik Kendaraan Ringan di SMK Negeri 1 Sumatera Barat. Jenis penelitian ini adalah deskriptif kuantitatif. Berdasarkan hasil analisis dapat disimpulkan bahwa persepsi siswa Kelas XI terhadap Implementasi Kurikulum 2013 Kompetensi Keahlian Teknik Kendaraan Ringan di SMK Negeri 1 Sumatera Barat berada pada kategori terlaksana baik (65.38%), dijabarkan dalam 6 indikator yaitu Model Pembelajaran pada kategori terlaksana baik (65.38%); Kompetensi Inti pada kategori terlaksana baik (50.00%); Pendekatan Saintifik pada kategori terlaksana baik (59.62%); Pengorganisasian Kelas pada kategori terlaksana sangat baik (67.31%); Penggunaan Sarana Prasarana pada kategori terlaksana baik (51.92%); Penilaian pada kategori terlaksana baik (32.69%).